Cognitive, Affective and Conative Loyalty in Higher Education Marketing: Proposed Model for Emerging Destinations - Manzuma-Ndaaba, Ndanusa Mohammed; Harada, Yoshifumi; Romle, Abd Rahim; Shamsudin, Abdul Shukor (International Review of Management and Marketing, 2016)
This study propose a synergy of behavioral relationships in line with researchers observation that application of marketing theories in education services needs more strategic exploration. The cognitive behavior which is rational, the affective behavior which is often irrational and the action behavior that increases business performances through enhanced profits and reductions in marketing communications cost is the perspective of this conceptual study. These linkages will not only increase the influx of international students to a study destination but will also raise switching barrier and make the preferred destination unique in a competitive international education environment. The proposal is to make emerging education destination countries to gain competitive advantages through identification and differentiation of unique services for continuous survival. The model is based on relationship marketing targeted at steady and long term contractual involvement build on satisfaction and commitment. Keywords: Cognitive, affective, conative, relationship marketing, emerging destinations JEL Classifications: J10, M10